Conventional and Doppler Abdominal Ultrasonography in Pacas (Cuniculus paca) - Rossi Feliciano, Marcus Antonio [UNESP]; Pereira da Camara Barros, Felipe Farias [UNESP]; Coutinho, Leandro Nassar [UNESP]; Soares de Brito, Marina Botelho [UNESP]; Uscategui, Ricardo Ramirez [UNESP]; Correia Santos, Victor Jose [UNESP]; Almeida, Vivian Tavares de [UNESP]; Kawanami, Aline Eyko [UNESP]; Nociti, Ricardo Perecin [UNESP]; Fernandes Machado, Marcia Rita [UNESP]; Russiano Vicente, Wilter Ricardo [UNESP] (Univ Fed Rio Grande Do Sul, 2014)
Background: The first report of ultrasound evaluation in pacas was for gestational diagnosis and monitoring. However, there are no reports of the use of this technique for the evaluation of abdominal structure in pacas. Elucidating the biology of wild species is important for preservation and potential use as experimental models for human and animal research. As such, this study aimed to describe an ultrasonographic view of major abdominal organs and determine the vascular indices of abdominal aorta and renal arteries in pacas (Cuniculus paca) by Doppler mode.Materials, Methods & Results: Fifteen adult females with a mean weight of nine kilograms were positioned into dorsal or lateral recumbency. A specific gel was applied, and transabdominal ultrasound examination was performed by a single experienced evaluator using MyLab 30 VET ultrasound equipment (ESAOTE, Italy) with 7.5 and 10.0 MHz linear transducers. Anatomy, biometry and ultrasonographic findings, such as ecogenicity, echotexture and wall thickness of main abdominal organs (bladder, kidneys, adrenals, spleen, liver, digestive system and ovaries), were assessed during the ultrasound scan. Doppler ultrasound was used to determine the peak systolic velocity (PSV), end-diastolic velocity (EDV), resistance index (RI = [PSV - EDV]/PSV) and pulsatility index (PI = [PSV - EDV]/mean velocity) of the abdominal aorta and renal arteries. The animals were healthy based on physical examination, hemogram and biochemical profile. Furthermore, we determined that the ultrasound technique for abdominal evaluation of these animals was feasible. Major abdominal organs were accessed using conventional ultrasonography biometric values and sonographic characteristics. Doppler examination was used to determine mean vascular indices of the abdominal aorta and the left and right renal arteries.Discussion: Several studies using the ultrasound technique in wild animals have demonstrated the clinical importance and applicability of this imaging method for veterinary medicine. As mentioned, ultrasound examination is feasible, effective and important for the assessment of topographical relations and ultrasound characteristics of abdominal organs in pacas. During urinary bladder ultrasound examination of the caudal abdomen, little repletion with anechoic content without sediment was observed, renal structures presented a topography, echogenicity and cortico-medullary relationship (1:1) and sonographic findings of the spleen and liver of pacas were similar to those described in dogs and cats. Upon digestive system ultrasound, the stomach showed sonographic characteristics similar to dogs such as peristaltic movements (3 to 5 per minute) and intestinal silhouettes (2 to 3 per min). The adrenal glands were easily detected by ultrasound, located cranial to the ipsilateral kidney, the same as in dogs, ferrets and coatis. Ovaries, as well as the internal follicular structures, were observed near the caudal renal pole. These findings corroborate the findings of normal ovaries in dogs and cats. Doppler mode of the abdominal aorta and renal arteries was feasible and useful for the study of the physiology and detection of hemodynamic abnormalities in pacas. Conventional and Doppler ultrasonography allowed the study of the abdominal structures of pacas (Cuniculus paca), providing original and valuable information on the topographic anatomy and morphophysiology of abdominal tissues and their sonographic descriptions. The results of this study may aid in abdominal injury evaluation in these animals and other wild species.
Keywords: paca; ultrasound; Doppler